Brothers, we are not professionals eaudiobook A plea to pastors for radical ministry. - Piper, John (christianaudio, 2013)
In this revised and expanded edition of Brothers, We Are Not Professionals that includes a new introduction and select all-new chapters, best-selling author John Piper pleads through a series of thoughtful essays with fellow pastors to abandon the professionalization of the pastorate and pursue the prophetic call of the Bible for radical ministry."We pastors are being killed by the professionalizing of the pastoral ministry," he writes. "The mentality of the professional is not the mentality of the prophet. It is not the mentality of the slave of Christ. Professionalism has nothing to do with the essence and heart of the Christian ministry. The more professional we long to be, the more spiritual death we will leave in our wake. For there is no professional childlikeness, there is no professional tenderheartedness, there is no professional panting after God."Brothers, we are not professionals. We are outcasts. We are aliens and exiles in the world. Our citizenship is in Heaven, and we wait with eager expectation for the Lord (Phil. 3:20). you cannot professionalize the love for His appearing without killing it. And it is being killed. "The world sets the agenda of the professional man; God sets the agenda of the spiritual man. The strong wine of Jesus Christ explodes the wine- skins of professionalism."